Parental support and acceptance of LGBTQ+ children: Integrated review - Singh Charan, Gopal; Kalia, Raman; Kumar, Rajesh; Kumar Dular, Sunil; Dutt Avasthi, Rishi; Kaur, Ekjot (Journal of Chitwan Medical College, 2024)
Society has made significant progress in Lesbian, Gay, Bisexual, Transgender, Queer, or Questioning (LGBTQ)+ acceptance and equality, but challenges persist, particularly in parental acceptance of LGBTQ+ children. This review examines the current landscape of parental acceptance and how such behaviour mitigates health risks for LGBTQ+ children. Cultural and social norms that perpetuate suffering underscore the urgent need for education and awareness, highlighting personal narratives and fostering empathy. The LGBTQ+ community continues to face mental health challenges due to systemic stigma, anxiety, guilt, and suicidal ideation, necessitating competent psychological support. Advocacy and allyship often focus on understanding misogyny and intersectionality, which pragmatically addresses discrimination while celebrating diversity. Increased awareness may lead to more tailored mental health support services. Creating inclusive environments is vital for the well-being of LGBTQ+ children, reminding us to continuously promote spaces where individuals can exist fully without policing. This review utilizes methodologies ranging from 2016 to 2023, sourcing data from PubMed, Web of Science, ProQuest, and Google Scholar. The study includes peer-reviewed articles, original research, systematic reviews, and meta-analyses, excluding non-peer-reviewed works and non-English publications.